A MESSAGE FROM THE AMERICAN INSTITUTE. - West, W. H. (The Accounting Review, 1926)
Abstract The article discusses about a message that was delivered during a speech by the president of American Institute of Accountants W.H. West. According to West, the Institute must be, of necessity, and of its on volition, interested in the work that peoples are doing for among the fundamental purposes of the Institution are two, the advancement of the science of accountancy and the development and improvement of education in accountancy. The extent to which people are living up to this desire is another matter. In this committee they have a very definite and good working contact with the Association. West is also proud about the library that the accountants have in their possession. It is not very easy for the man who is not in the City of New York to avail himself the library of the Institute. The Committee on Endowment, who administer the affairs of the library have given instructions to librarians to acquire every publication, every book, every pamphlet, every article that is written on accountancy or related subjects and place them on the shelves so that they might be available. This means that with the system of indexing by subject, author, publication, etc. the matters are readily able to find anything that is published which one might ask for.